Reasons for not Opting for Crown Following Root Canal Treatment - Ahmed, Haseeb Arshad, Mateen Ahmad, Fatima Hafiz, Sarah Rabbani, Amna Nauman Khan (Pakistan Journal of Medical & Health Sciences, 2022)
This study was conducted to know the reasons why people do not opt for crowns after root canal treatment. A well-formed proforma was used to document the ratio of crowned vs. non-crowned individuals and the reason behind each. A total of 151 participants with RCT treated teeth took part in the survey. almost half of them got their RCT treated teeth crowned (51.0%). 49.0% did not get their teeth crowned and 21.2% showed a lack of interest. Other reasons identified were lack of awareness, time limitations and non-availability of facilities. Lack of awareness is a far more common cause that can be minimised by good education and guidance.